The use of calcined oyster shell and rock flour to improve the nutritive value of rice straw preserved in airtight wrapping for feeding cattle under a tethered herding system - Khalil Khalil; Ananta Dwi; Andri Andri; Hermon Hermon (BIO Web of Conferences)
Rice straws are a cheap source of fodder, but they are underutilized as feed due to their low voluntary intake and susceptibility to physical and microbial damage. The present study aimed to define the beneficial effect of calcined oyster shells and rock flour as preservative agents to maintain the physical appearance, palatable component, moisture, nutrient content, and nutritional value of rice straw preserved in an airtight wrapping method. Rice straws in intact and fresh form were sprayed with 1.2% molasses and 0.15% urea solution and sprinkled with 1% calcined oyster shell (cOS), 1% calcined rock flour (cRF), and a mixture of 0.5% cOS+0.5% cRF. The straws were preserved in airtight wrapping for 60 days. Fresh and preserved straws were assessed for organoleptic values, botanical fractions, and proximate and fiber fraction content. The nutritive values were evaluated through a feeding trial using young Pesisir bulls reared under a tethering herding system. There were four experimental diets: fresh rice straw (FRS), cOS preserved rice straw, cRF preserved rice straw, and cOS+cRF preserved rice straw. Parameters measured included DM intake, weight gain, blood hematology, protein, and mineral profiles. Results found that preserved rice straws had higher moisture and crude protein content than fresh straws. Preserved rice straws supplemented with a mixture of calcined shells and rock flour had significantly better texture and microbial status than that of either calcined shell or rock flour. Feeding preserved rice straw supplemented with a mixture of calcined shells and rock flour improved body weight gain that was not significantly different from the fresh straw. In conclusion, using preservatives as a mixture of calcined shells and rock flours produces the best-preserved rice straw for feeding cattle.